Government policy direction in Botswana, Namibia, and South Africa to their San communities : local implications of the International Indigenous Peoples' Movement - Hartley, Bonney Elizabeth (Department of Political Studies, 2014)
Word processed copy. Includes bibliographical references (leaves 97-103).